Production and purification of xylooligosaccharides from oil palm empty fruit bunch fibre by a non-isothermal process - Ho, Ai Ling (2014)
Oil palm empty fruit bunches (OPEFB) fibre, a by-product generated from non-woody, tropical perennial oil palm crop was evaluated for xylooligosaccharides (XOS) production. Samples of OPEFB fibre were subjected to non-isothermal autohydrolysis treatment using a temperature range from 150 to 220 ºC. The highest XOS concentration, 17.6 g/L which relayed from solubilisation of 63 g/100 g xylan was achieved at 210 ºC and there was a minimum amount of xylose and furfural being produced. The chromatographic purification which was undertaken to purify the oligosaccharide-rich liquor resulted in a product with 74–78% purity, of which 83–85% was XOS with degree of polymerisation (DP) between 5 and 40.